Jumpstart RTI using RTI in your elementary school right now - Hall, Susan L.
Susan L. Hall asserts that an educator's job is not done until a school's RTI practices result in at least 95 percent of its students reading at benchmark levels. This book's research-based strategies will get you started on the road to achieving those results quickly, efficiently, and successfully. Included are case studies, delivery models, practical tools, reproducibles, analysis worksheets, and forms that can be downloaded from a secure website